Caracterização limnologicas e da pesca artesanal em um reservatório no semiárido tropical - Lopes, Yuri Vinicius de Andrade (Universidade Federal Rural do Semi-Árido, 2016)
The influence of temporal and spatial gradients of the abiotic variables was evaluated in an artificial reservoir in tropical semi-arid region, located in the state of Rio Grande do Norte - BR. In relation to data on fisheries was held monthly during the course of one year (January 2012 to December 2012) through interviews with artisanal fishermen that use the reservoir as explored environment. Through the artisanal fishing landing, was sampled a total of 9932.65 kg fish, was parallel obeisant environmental data trying to find the relationship from entering the capture and environmental variables. Environmental variables were analyzed by Principal Component Analysis (PCA). The species caught in the reservoir were the peacock bass, tilapia, hake, curimatã and piau. The first two axes of the PCA explained 78.58% of the total variation of environmental data related to the reservoir. Axis 1 was positively influenced by pH, total dissolved solids (TDS), total N, total-P, and negatively influenced by dissolved oxygen (DO), temperature and precipitation. Once the first four variables (pH, total dissolved solids (TDS), total-N, total-P) presenting a high level of redundancy, the two variables with minor amounts (total N, P total) were excluded for further analysis. The transparency and conductivity were the variables that most influenced the Axis 2, while Chlorophyll, showed no interaction with any of the two axes. According to the CCA, the abiotic oxygen factors dissolved, electrical conductivity and temperature, favored the increase of the capture of species curimatã, tilapia and piau these more factors transparency favored catch hake while the pH and total dissolved solids favored the increase in the catch of the peacock bass. Thus the results demonstrate that the environmental variables influence the capture of the species composition in the reservoir during the study Santa Cruz. During the second study The survey data was conducted on a quarterly basis over the years 2011 to 2014. Sampling was carried out in eight points distributed in the reservoir. Environmental variables observed in the study showed no difference in the spatial distribution. However, when observed in the temporal sense of statistical analysis indicated difference between the years in the reservoir. The rainfall proved to be a determining factor in the temporal dynamics of abiotic variables in the reservoir of Santa Cruz, mainly temperature; pH; Dissolved oxygen; oxygen saturation; electrical conductivity and total dissolved solids. The reservoir of Santa Cruz, showed a trend of increase in total dissolved solids concentrations, high electrical conductivity and pH, characteristics that indicate eutrophication trend in this environment
Characterization limnological and artisan fishing in a reservoir in tropical semiarid
Keywords: Variáveis ambientais; Pesca; Captura; Santa Cruz; Pluviometria; Balanço Hídrico; Variable environmental; Fishing; Catch; Santa Cruz; Rainfall; Water balance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA